KAJIAN PERTUMBUHAN DAN SERAPAN HARA BEBERAPA VARIETAS PADI LOKAL PADA BERBAGAI DOSIS NITROGEN - Bustami Bustami; Ainal Mardhiah (Jurnal Agrotek Lestari, 2018)
This study was conducted to assess effects of nitrogen fertilizer doses and local Aceh rice varieties on growth, nutrient uptake and efficiency uptake of nitrogen. Experiment was conducted in Aneuk Glee Village, Indrapuri Sub District, Aceh Besar District. Nitrogen uptake analysis was conducted at Laboratory of Soil Research Center, Bogor. Experimental design used was a split plot design with three replications. Factors evaluated consisted of nitrogen fertilizer doses (0 kg ha-1, 90 kg ha-1 and 180 kg ha-1) as main plots and varieties (20 varieties)as subplot. Data were collected for plant height, number of tillers, fresh weight biomass, dry weight biomass, nutrient uptake and nitrogen uptake efficiency. Results showed that nitrogen fertilizer dose exerted highly significant effects on plant height at ages 35 and 49 days after transplanting (DAT), number of tillers at ages 10, 20 and 30 DAT and significant effects on plant height age 21 DAT, fresh and dry weight biomass and nitrogen uptake efficiency. Varieties exerted a highly significant effect on plant height at age 35 DAT and significant effects on fresh and dry weight biomass. There was no significant interaction between doses of nitrogen fertilizer and varieties on all variables observed.